Mengulas Ekstraksi Niat Pembelian Skincare (Studi Kasus Pada Gen Z Pria) - Rahmantari, Ni Luh Laksmi; Susila Putra, I Putu Dharmawan Suryagita; Utari, Ni Komang Mela Tri; Mardika, Agus Putra; Yasmita, I Gusti Ayu Lia (Universitas Pahlawan Tuanku Tambusai, 2024)
Skincare purchases by Gen Z men have increased rapidly in recent years. Gen Z, born between 1997 and 2012, is an influential young generation who is familiar with the digital era and has wide access to information and skincare products. With sales increasing at around 15% per year, more and more Gen Z men care about the health of their skin and face. However, previous research has focused more on skincare purchases in general, not specifically on men. Therefore, it is important to research the skincare purchase intentions of Gen Z men.